2006
DOI: 10.1021/jo0620009
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Efficiency of the Aryne Chemistry of (Dehydro)octafluoro[2.2]paracyclophane When Using the Cadogan Method

Abstract: Generation of the aryne, (dehydro)octafluoro[2.2]paracyclophane, from its acetamide derivative utilizing the Cadogan method led to remarkable results with respect to Diels-Alder and ene reactivity. A comparison was made between this new and virtually unused method and our earlier reported results using Cram methodology (reaction of aryl iodide with potassium tert-butoxide). Surprisingly, no ene reactivity was observed with the Cram methodology. This mechanistic conundrum was examined extensively with no unambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…This is the geometry found by a conformational search using MM2 in Hyperchem, and confirmed by the NOEs displayed by the products of the reaction of the AF4 arene with cyclopentene and with cyclohexene [2]. Two NOEs between 3.06 and 7.21 and between 5.50 and 7.11 allowed the assignment of the protons on the face of the other para-phenylene moiety of the AF4, as 7.21 being syn to 3.06.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…This is the geometry found by a conformational search using MM2 in Hyperchem, and confirmed by the NOEs displayed by the products of the reaction of the AF4 arene with cyclopentene and with cyclohexene [2]. Two NOEs between 3.06 and 7.21 and between 5.50 and 7.11 allowed the assignment of the protons on the face of the other para-phenylene moiety of the AF4, as 7.21 being syn to 3.06.…”
Section: Resultssupporting
confidence: 70%
“…This is the geometry found by a conformational search using MM2 in Hyperchem, and confirmed by the NOEs displayed by the products of the reaction of the AF4 arene with cyclopentene and with cyclohexene [2]. In compound 9, 1.97 displays NOEs with two aromatic protons at 7.08 and 7.40, while 1.67 does not, therefore, the other para-phenylene ring of the AF4 moiety bound to the cyclopropyl ring is on the same side of this ring as 1.97.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The spectroscopy of these compounds is particularly interesting, and nuclear magnetic resonance (NMR) is no exception . With the advancements in syntheses of bridge‐fluorinated [2.2] paracyclophanes, and their potential utility as monomers in high‐performance polymers, the spectroscopy of this class of compounds has been an area of particular interest. The presence of fluorine atoms in this class of cyclophanes render these compounds amenable to study by 19 F NMR, which is highly sensitive and intrinsically information‐rich, and provides unique insight into their chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, our broad studies of octafluoro [2.2]paracyclophane (AF4) and its derivatives have demonstrated that the highly electron-deficient aromatic rings of AF4 exhibit a rich diversity of chemical behavior, including clean, high yield electrophilic substitution and disubstitution [1,2] unique aryne reactivity [3] and excellent S RN 1-reactivity with soft nucleophiles such as phenyl thiolate and malonate anion (Scheme 1) [4]. In the present communication, we wish to report the unexpected discovery of an unusual ring-opening reaction of nitro-AF4 when it is treated with hard nucleophiles, such as alkoxides and cyanide ion.…”
Section: Introductionmentioning
confidence: 99%